Rancangan Game Labirin Menggunakan Scracth 3 Berbasis Android - Fauzi Anggi Ariesta; Firdiyan Syah (Universitas PGRI Yogyakarta, 2022)
Indonesia has 34 provinces, each of which has its own culture and customs. One of the cultures that still exists today is traditional clothing. Indonesian people need to know and recognize the various kinds of traditional clothing that exist so that the culture does not become extinct. This study aims to build a maze runner game using scratch 3. Methods of data collection using literature study and observation. The application development phase includes analysis, system design, implementation, and testing. The application can be played using an android smartphone Testing the application design shows that this application is feasible and can be used as a medium of entertainment as well as a medium of knowledge to introduce various kinds of traditional clothing in Indonesia to its users.